Efeitos de deformação nas propriedades magnéticas de pontos quânticos em bicamadas de grafeno - Nascimento, Jonas da Silva (2017)
The magnetic properties of graphene-based nanostructures present di erent features from bulk graphene, because of surface, or, more properly, edge states. Wheras bulk graphene is a diamagnetic semimetal, nanoribbons with zigzag edges have two at bands at the Fermi energy, i.e., are paramagnetic metals. It was also report that the number and the properties of edge states are sensitive to the geometry of the mono and bilayer GQD, such that geometry and edge type play an import role in the diamagnetic response of the graphene nanostructures. In this work, we study the magnetic properties of nite-size bilayer graphene quantum dots (BLG QD) with di erent geometrical shapes: hexagon, triangle and square, by considering two di erent type of edges and stacking: zigzag and armchair, and AAand AB-stacking layers, respectively, both in the presence and absence of a certain lattice deformation. In our work, we use the tight-binding approach coupled with electronic interaction term, that is described by the mean- eld approximation of the one-orbital Hubbard model, in order to investigate how the magnetic properties, such as magnetization and the energy states, are a ected by the presence of an uniaxial strain, in particular, applied along the zigzag edge direction. Our ndings show that the magnetic properties depends on the geometry and not only on the existence of zigzag edges, as also observed for monolayer graphene QDs. In the absence of strain, the magnetization as a function of the Hubbard term present di erent (equal) minimum on-site Coulomb repulsion Uc for the (AB-)AA-stacked BLG QDs with zigzag edges (for both edge type). When strain is applied, the nearest-neighbor hopping integrals are naturally modi ed that leads to a modi cation of the local magnetic moments and consequently on the magnetic properties. Our results show that the magnetization is enhanced under uniaxial strain and exhibits two di erent regimes by increasing the amplitude of the deformation for all studied geometries